Influence of salinity on the growth and biochemical composition of the cyanobacterium Synechococcus sp. - Néstor Rosales; José Ortega; Roberta Mora; Ever Morales (Ciencias Marinas, 2005)
The study of cyanobacteria isolated from hypersaline environments is of interest because of their metabolic and ecophysiologic versatility in adapting to extreme conditions of salinity, temperature, irradiance and nutrient availability. The effect of salinity at 0‰, 35‰, 70‰ and 100‰ on the growth, dry weight, and pigment, protein, carbohydrate and lipid production of the cyanobacterium Synechococcus sp. was determined. Bioassays were kept in ALGAL medium equivalent to 8 mM NaNO3, constant aeration, 12:12 h photoperiod, 28 ± 2ºC and 156 µmol quanta m–2 s–1 of irradiance. The cyanobacterium was able to grow under all salinities tested. Cell density was optimized at 35‰, with 607.64 ± 14.35 cells mL–1. The highest values of dry weight (3.87 ± 0.03 ng cell–1), chlorophyll a (41.86 ± 0.39 fg cell–1), ß-carotene (9.03 ± 0.15 fg cell–1), zeaxanthin (9.74 ± 0.24 fg cell–1), proteins (1.95 ± 0.05 pg cell–1) and carbohydrates (1.80 ± 0.05 pg cell–1) were obtained at 100‰; however, the highest lipid content (0.45 ± 0.04 pg cell–1) was reached at 0‰. This Synechococcus strain shows halotolerance and the capacity to modulate the production of enriched biomass with pigments, proteins, carbohydrates and lipids in terms of salinity.